Dampak Lalu Lintas Pembangunan Rumah Sakit Nur Hidayah Bantul Terhadap Ruas Jalan Yogyakarta – Barongan Dengan Metode PKJI 2023: Traffic Impact Of The Construction Of Nur Hidayah Hospital In Bantul On The Yogyakarta – Barongan Road Section Using The 2023 PKJI Method - Azri Novadli (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The construction of Nur Hidayah Bantul Hospital is located on Jalan Yogyakarta–Barongan, Bembem, Trimulyo, Jetis District, Bantul Regency, Special Region of Yogyakarta, which is expected to have a significant impact on the surrounding road network. Nur Hidayah Bantul Hospital has a land area of ​​2131 m2 with a building area of ​​5110 m2 and is planned to have 5 floors. The construction process will involve intensive construction activities, such as the mobilization of heavy equipment, transportation of materials, and the entry and exit of workers. This will cause construction traffic generation that will affect the smooth flow of vehicles on the road network, especially the Yogyakarta–Barongan Road section. The government has emphasized that every planned development of activity centers, settlements and infrastructure that will cause disruption to security, safety, order, and smooth traffic and road transportation must be subject to a traffic impact analysis as regulated in the Minister of Transportation Regulation No. 17 of 2021. The purpose of this study is to analyze the existing traffic performance on the Yogyakarta-Barongan Road Section, as well as to analyze changes in traffic performance on the Yogyakarta-Barongan Road Section due to the construction of the Nur Hidayah Bantul Hospital using the 2023 PKJI method. The results of the study showed a decrease in road performance during the construction of the Nur Hidayah Bantul Hospital compared to existing conditions, with a DJ value of 0.48 during the existing period and 0.52 during construction.